Planetary protection: an international concern and responsibility - Coustenis, Athena; Hedman, Niklas; Doran, Peter T.; Al Shehhi, Omar; Ammannito, Eleonora; Fujimoto, Masaki; Grasset, Olivier; Groen, Frank; Hayes, Alexander G.; Ilyin, Vyacheslav; Kumar, K. Praveen; Morisset, Caroline-Emmanuelle; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Planetary protection is a set of measures agreed upon at an international level to ensure the protection of scientific investigation during space exploration. As space becomes more accessible with traditional and new actors launching complex and innovative projects that involve robotics (including sample return) and human exploration, we have the responsibility to protect the pristine environments that we explore and our own biosphere. In this sense, the Committee on Space Research (COSPAR) provides the international standard for planetary protection as well as a forum for international consultation. COSPAR has formulated a Planetary Protection Policy with associated requirements for responsible space exploration. Although not legally binding under international law, the standard offered by the Policy with its associated requirements is internationally endorsed along with implementation guidelines supplied for reference in support States’ compliance with Article IX of the United Nations Outer Space Treaty of 1967. Indeed, States parties to the Outer Space Treaty (under Article VI) are responsible for any space activities in their countries, governmental and non-governmental. The main goal of this Policy is to avoid compromising the search for any lifeforms on other celestial bodies and to protect the Earth from a potential threat posed by extraterrestrial samples returned by an interplanetary mission. The COSPAR Planetary Protection Policy has defined five categories, depending on the target and objective of the specific space mission. Associated to these categories are requirements are various degrees of rigor in the contamination control applied. The Policy is assessed regularly and updated with input from new scientific findings and in conjunction with the fast-evolving space exploration milieu. The COSPAR Panel on Planetary Protection (PPP) is a designated international committee composed of scientists, agency representatives and space experts. Its role is to support and revise the COSPAR Policy and its related requirements (https://cosparhq.cnes.fr/scientific-structure/panels/panel-on-planetary-protection-ppp/). The Panel’s activities deal with the individual needs of a space mission while exercising swift care and expertise to ensure sustainable exploration of the Solar System.